EVALUASI PENDIDIKAN FARUD DALAM PERSIAPAN MENGHADAPI FRAUD DI DUNIA KERJA UNTUK MAHASISWA JURUSAN AKUNTANSI UNIVERSITAS SURABAYA - Fransiska Dwi Utari (Perpustakaan Universitas Surabaya, 2016)
Accounting scandals in the world make people underestimate about accounting profession. The Association of Certified Fraud Examiner (ACFE), which is the largest nongovermental organization in the world with 31.000 members, report that organizations always lost 5% of their income in a year because of fraud. This research objective is to improve the mindset of accounting student, as accountants in the future, so they assume that fraud is a serious problem and not a good thing to do. If they think like that, it will make them have the intention to prevent fraud, resolve cases of fraud, or even they commit fraud. Even if an accountant behaves athically, they should know how to behave when faced with fraud in their carrer. This research was carried out by observing the accounting department in Universitas Surabaya (UBAYA). This research used 9 student from different groups of GPA. It also surveyed the subject that teach aboutfraud as the main discussion. The findings show that Universitas Surabaya focus to educate their student with fraud prevention, as they teach how to create a strong system to minimalize fraud. Universitas Surabaya believe in the philosophy of “prevent is better than cure”.